Effects of a New Emollient-Based Treatment on Skin Microflora Balance and Barrier Function in Children with Mild Atopic Dermatitis - Bianchi, Pascale; Theunis, Jennifer; Casas, Christiane; Villeneuve, Cecile; Patrizi, Annalisa; Phulpin, Chloe; Bacquey, Adeline; Redoulès, Daniel; Mengeaud, Valerie; Schmitt, Anne-Marie (Pediatric dermatology, 2016)
Background/Objectives The use of emollients is widely recommended for the management of atopic dermatitis (AD), especially between flares. An imbalance of skin microflora is suspected of playing a key role in exacerbations of AD. Our aim was to evaluate the effect of a new emollient balm on clinical parameters (SCORing Atopic Dermatitis [SCORAD], xerosis, pruritus), skin barrier function (transepidermal water loss and loricrin, filaggrin, corneodesmosin, and involucrin expression], skin microflora biodiversity, and Staphylococcus aureus and Staphylococcus epidermidis balance in children with mild AD. Methods Fifty‐four children (1–4 yrs old) were enrolled in this randomized, controlled study. Subjects applied a hygiene product and the emollient balm (emollient group, n = 28) or the hygiene product only (control group, n = 26) twice a day for 28 days. Results We found improvement in favor of the emollient group in SCORAD (p < 0.001), pruritus (p = 0.06), and xerosis (p = 0.06) after 28 days of application. Moreover, transepidermal water loss decreased in the emollient group by 34% (p = 0.06) and involucrin expression by 37% (p = 0.001) at day 28 from baseline in association with improvement in barrier function, whereas other barrier‐specific proteins did not vary. S. aureus increased significantly in the control group only (6.5 times, p = 0.01), whereas S. epidermidis remained stable in both groups. The Shannon index (H′ = 2.3) did not vary with treatment in either group. Conclusion Twice‐daily application of a new emollient balm in children with mild AD protected the skin from S. aureus proliferation and preserved microflora biodiversity.